Psammomatoid juvenile aggressive ossifying fibroma of mandible - Rao, Sudhapalli Chidanand (Medknow Publications & Media Pvt Ltd, 2012)
A female patient, aged 14 years, came to dental OPD, with a large swelling of the right mandibular region, progressing since 4–5 years. The swelling initially started with a small size and later it became a large swelling extending from left lower premolar region to right mandibular angle region. Inferiorly, the swelling was extending below the inferior border in the symphysis region. No paresthesia was experienced by the patient. There was quite a marked facial disfigurement of the right mandibular body and symphysis region extending to left side. No other bones were involved and no other abnormalities were found on general physical examination. The medical history was noncontributory. There was no family history of skeletal disease. The case was surgically treated by segmental resection of the mandible and reconstruction was done using stainless steel reconstruction plate. With the follow-up period of 1 year, there was no recurrence.